Estudo comparativo entre as propriedades de concretos produzidos em laboratório e em canteiro de obras - Oliveira, Rafaela Leite de (Universidade Federal Rural do Semi-Árido, 2017)
Currently, most of the concrete used in construction works are produced in machining centers. However, in works of smaller size or at the option of the builder himself, the concrete produced at the construction site can also be used, which can be done with the aid of a concrete mixer, the so-called concreted concrete, or can count on the method of manual mixing, performed by the project'sm employees. This study analyzes and compares these two methods of concrete production, the manual, produced in the laboratory of UFERSA - CMPF, and the mechanic, produced in the construction site of a residential project, using the same trait in both. For this, 10 specimens were made, 5 CP’s of manual concrete and 5 CP’s of concrete. The following tests were performed: slump test and specific mass for concrete in the fresh state, and the tests: absorption, porosity, specific mass and compressive strength for concretes in the hardened state, after being submitted to 28 days of submerged cure. The concreted concrete, produced in construction site, presented a higher plasticity of the paste, about 77% more than manual concrete, and consequently, a higher workability, but in the hardened state, presented values of resistance below the design resistance, reaching only 53,12% of this value, which proves the need to be carrying out the technological control of the concrete production at the construction site, be it through mechanical or manual mixing, since the lack of this control can bring unsatisfactory results, and well below expected.
Keywords: Concreto manual; Concreto betonado; Produtividade; Controle tecnológico; Manual concrete; Concreted concrete; Productivity; Technological control; ENGENHARIAS::ENGENHARIA CIVIL